Non-stationary heat transfer in a hollow cylinder with functionally graded material properties. - Ostrowski, Piotr; Michalak, Bohdan (Polskie Towarzystwo Mechaniki Teoretycznej i Stosowanej, 2011)
The unidirectional non-stationary heat conduction in a two-phase hollow cylinder is considered. The conductor is made of two-phase stratified composites and has smooth gradation of effective properties in the radial direction. Therefore, we deal here with a special case of functionally graded materials, FGM. The formulation of mathematical model of the conductor is based on a tolerance averaging approach (TAA). Application to the non-stationary heat conduction and a comparison of the tolerance model with the asymptotic one is shown. The effect of geometry and material properties of the conductor on the temperature field is examined.

W pracy rozważano niestacjonarne przewodzenia ciepła w dwuskładnikowym wydrążonym cylindrze. Przewodnik jest wykonany z dwuskładnikowego warstwowego kompozytu mającego łagodną zmienność efektywnych własności w kierunku promieniowym. Stąd mamy tutaj do czynienia ze specjalnym przypadkiem materiału o funkcyjnej gradacji własności (ang. functionally graded materiale, FGM). Zbudowanie uśrednionego modelu matematycznego rozpatrywanego przewodnika jest oparte na technice tolerancyjnej aproksymacji. W pracy pokazano zastosowanie otrzymanego modelu tolerancyjnego i porównanie wyników z wynikami dla modelu asymptotycznego w przypadku niestacjonarnego przewodzenia ciepła. Zbadano wpływ zmienności geometrii i własności materiałowych przewodnika na pole temperatury.
Niestacjonarny przepływ ciepła w wydrążonym cylindrze wykonanym z materiału o funkcyjnej gradacji własności.
Keywords: heat transfer; functionally graded material; tolerance averaging approach; przepływ ciepła; niestacjonarne przewodzenie ciepła; dwuskładnikowy wydrążony cylinder; materiał o funkcyjnej gradacji własności; technika tolerancyjnej aproksymacji; model tolerancyjny; model asymptotyczny